APLIKASI DAN PANDUAN PEMBUATAN RAPORT BERBASIS EXCEL PADA SDS AS SALAM PAMULANG TANGERANG SELATAN - Simon Simarmata; Jamaludin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The system for receiving report cards in the current era of technological advances is very important that can be viewed and distributed digitally to avoid using paper. Report cards contain numbers which are the results of student learning for one semester. There is one benchmark in seeing the educational development of our sons or daughters, namely through the value of the report card. Whether we are good or not, whether our children are smart or not is based on the numbers printed on the report card. It seems that the value of the report card is a silent witness that explains how the educational process of our sons or daughters is in following the lessons. There is no rank in the 2013 Curriculum for report cards. One of the reasons is that it is impossible for humans to master and be smart in every field. So in the ranking system, it's as if the first rank masters and is smart in all subject areas. Now there are no more champions, no applause and no prizes. According to KBBI, the meaning of a report card is a book that contains the value of intelligence and student achievement at school, which functions as a teacher's report to parents or guardians of students. Report cards are generally gifts from someone who has spent time together, whether in teaching and learning, discussions, or through research. Someone who knows the strengths and weaknesses of their students. The report card itself is one of the school's responsibilities to the community regarding the abilities that students already have in the form of a set of assessment results. Assessment activities are carried out through measuring or testing students after participating in the learning process in a particular unit. Report cards have their own function for each person.